Psoriasis patients with nail disease have a greater magnitude of underlying systemic subclinical enthesopathy than those with normal nails. Issue 4 (9th December 2011) - Ash, Zoe R; Tinazzi, Ilaria; Gallego, Concepción C; Kwok, Chung; Wilson, Caroline; Goodfield, Mark; Gisondi, Paolo; Tan, Ai Lyn; Marzo-Ortega, Helena; Emery, Paul; Wakefield, Richard J; McGonagle, Dennis G; et al.
Abstract : Objective: Enthesopathy is a major feature of psoriatic arthritis (PsA), which is supported by imaging studies. Given that nail disease often predates PsA and that the nail is directly anchored to entheses, the authors asked whether nail involvement in psoriasis equates with a systemic enthesopathy. Methods: Forty-six patients with psoriasis (31 with nail disease) and 21 matched healthy controls (HC) were recruited. 804 entheses of upper and lower limbs were scanned by an ultrasonographer blinded to clinical details. Results: Psoriasis patients had higher enthesitis scores than HC (median (range) 21 (0–65) vs 11 (3–39), p=0.005). Enthesopathy scores were higher in patients with nail disease (23 (0–65)) than in patients without nail disease (15 (5–26), p=0.02) and HC (11 (3–39), p=0.003). Inflammation scores of patients with nail disease (13 (0–34)) were higher than patients without nail disease (8 (2–15), p=0.02) and HC (5 (0–19), p<0.001). Modified nail psoriasis severity index scores were correlated to both inflammation (r 2 =0.45, p=0.005) and chronicity scores (r 2 =0.35, p=0.04). No link between the psoriasis area and severity index and enthesitis was evident. Conclusion: The link between nail disease and contemporaneous subclinical enthesopathy offers a novel anatomical basis for the predictive value of nail psoriasis for PsA evolution.